Outcome of paediatric acute flaccid myelitis associated with enterovirus D68: a case series. (12th November 2018) - Kirolos, Amir; Mark, Kate; Shetty, Jay; Chinchankar, Nandita; Mcdougall, Catherine; Eunson, Paul; Stevenson, Janet; Templeton, Kate; ,
Abstract : Enterovirus D68 (EV‐D68) is an emerging infection associated with acute flaccid myelitis (AFM). Cases of AFM associated with EV‐D68 infection have increased in recent years and the evidence for a causal link is growing. However, our understanding of the epidemiology, clinical features, prognosis, and neurological sequelae of EV‐D68 requires ongoing surveillance and investigation. We report five cases of AFM in previously typically developing children (2–6y) from South East Scotland during September and October 2016 after infection with EV‐D68 (all detected in the nasopharyngeal aspirates). All cases presented with significant neurological symptoms, which were severe in two cases requiring intensive care support because of respiratory paralysis. At 18‐month follow‐up, two cases remain ventilator‐dependent with other cases requiring ongoing community rehabilitation. These cases represent one of the largest reported paediatric cluster of AFM associated with EV‐D68 in Europe. The epidemiology and clinical information add to the knowledge base and the 18‐month outcome will help clinicians to counsel families. What this paper adds: Nasopharyngeal aspirate is more sensitive for viral isolation and isolated in all cases. Clinical outcome at 18 months after enterovirus D68 with acute flaccid myelitis provides information on extent of recovery and level of disability. What this paper adds: Nasopharyngeal aspirate is more sensitive for viral isolation and isolated in all cases. Clinical outcome at 18 months after enterovirus D68 with acute flaccid myelitis provides information on extent of recovery and level of disability. This article is commented on by Okumura and Mori on pages290–291 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.